2018
DOI: 10.1186/s12885-018-4170-7
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of topoisomerase II alpha protein in early stage luminal breast cancer

Abstract: BackgroundTopoisomerase II alpha (TOP2A) protein has been shown to be a proliferation marker associated with tumor grade and Ki67 index. The prognostic effect of TOP2A seems different among different subtypes of breast cancer. The current study evaluated the prognostic impact of TOP2A protein on luminal breast cancer.MethodAltogether 434 stage I-II luminal breast cancer patients who underwent curative surgery in Sun Yat-Sen University Cancer Center between 2007 and 2009 were enrolled. TOP2A protein expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 38 publications
2
51
0
Order By: Relevance
“…EFNA3 is upregulated in Subtype-2, and previous studies show that it contributes to the metastatic spread of breast cancer [19]. Our model predicted that increased expression of LGR4, TESC, TOP2A, and ZNF695 is suggestive of increased invasive and metastatic activity in Subtype-2 [20]. Decreased expression of FGF10 is seen in Subtype-2 and predicted by our model is suggestive of dysplasia in LUAD subtype-2 samples [21].…”
Section: Resultssupporting
confidence: 53%
“…EFNA3 is upregulated in Subtype-2, and previous studies show that it contributes to the metastatic spread of breast cancer [19]. Our model predicted that increased expression of LGR4, TESC, TOP2A, and ZNF695 is suggestive of increased invasive and metastatic activity in Subtype-2 [20]. Decreased expression of FGF10 is seen in Subtype-2 and predicted by our model is suggestive of dysplasia in LUAD subtype-2 samples [21].…”
Section: Resultssupporting
confidence: 53%
“…Topoisomerase-targeting anti-cancer drugs have been successfully used in the clinic, and their efficacy is based on topoisomerase poisoning (22). Recently, it has been reported that abnormal alterations and modifications of TOP2A may be critical to chromosome instability in some cancer types (23).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of abnormal topoisomerase plays a critical role in chromosome instability and tumorigenesis which has been shown to be a proliferation marker associated with the tumor grade [ 45 , 46 ]. Currently, the topo II-targeting drugs can be divided into two categories including poisons such as etoposide, mitoxantrone, and doxorubicin and catalytic inhibitors such merbarone and aclarubicin [ 23 ].…”
Section: Discussionmentioning
confidence: 99%